2013
DOI: 10.1136/bcr-2013-008857
|View full text |Cite
|
Sign up to set email alerts
|

Pathological fractures as an initial presentation of Wilson's disease

Abstract: Wilson's disease (WD) has varied phenotypic presentations. Here we report the case of a 16-year-old boy who presented with a history of multiple pathological fractures, severe joint deformities, hepatic dysfunction, cognitive decline and limb dystonia. On examination, the patient had pinched out facies, pallor and leukonychia totalis. Bilateral Kayser Fleischer (KF) ring was present. Musculoskeletal examination revealed pectus carinatum, bilateral genu valgus and gun-stock deformity of the left elbow joint. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Although musculoskeletal features may be well-developed in Wilson's disease, this has limited consideration. Accepted musculoskeletal manifestations of Wilson's disease include the following: bone demineralization (14), genu varum (15), scoliosis (16), synovitis (17), osteochondritis dissecans (18), osteomalacia and rickets (19,20), avascular necrosis of femoral head (21), early osteoarthritis (17), spontaneous fracture (21)(22)(23), heterotopic ossification (24), osteoporosis (25), and epiphyseal dysplasia (26).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Although musculoskeletal features may be well-developed in Wilson's disease, this has limited consideration. Accepted musculoskeletal manifestations of Wilson's disease include the following: bone demineralization (14), genu varum (15), scoliosis (16), synovitis (17), osteochondritis dissecans (18), osteomalacia and rickets (19,20), avascular necrosis of femoral head (21), early osteoarthritis (17), spontaneous fracture (21)(22)(23), heterotopic ossification (24), osteoporosis (25), and epiphyseal dysplasia (26).…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Relatively well-known musculoskeletal manifestations of WD include synovitis,[ 9 ] early osteoarthritis,[ 9 ] osteoporosis,[ 10 ] rickets and osteomalacia. [ 11 ] Lesser known manifestations include spontaneous fracture,[ 12 ] heterotopic ossification,[ 13 ] scoliosis,[ 14 ] epiphyseal dysplasia,[ 14 ] genu varum,[ 15 ] avascular necrosis of femoral head [ 15 ] and osteochondritis dissecans. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The patient already had subtle neurological signs of WD, however it was diagnosed while investigating the cause of osteoporosis in the patient. Verma et al [ 12 ] reported a case of a 16-years-old male presenting with pathological fracture of the humerus along with full-blown hepatic, neuropsychiatric and ophthalmic features of WD.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia [ 18 ], ischemic cardiomyopathy [ 153 ], kidney recipients taking immunosuppressives [ 28 , 84 ], hepatitis C [ 154 ], Wilson’s disease [ 155 ]…”
Section: Clinical Presentationsmentioning
confidence: 99%